Influenza A(H1N1)pdm09 infection in pregnant and non-pregnant women hospitalized in Singapore, May – December 2009. Issue 6 (June 2015) - Lim, C.; Ang, L.W.; Tey, S.H.; James, L.; Kanagalingam, D.; Su, L.L.; Tan, H.K.; Yong, E.L.; Lim, M.L.
Abstract Objectives The aim of this study was to compare the demographic and clinical characteristics of pregnant women and non-pregnant women of childbearing age hospitalized with laboratory-confirmed influenza A(H1N1)pdm09 infection in Singapore, and to assess whether pregnancy was a risk factor associated with the development of influenza-related complications. Study design Retrospective observational study. Methods We retrospectively identified and collected information from available medical records of all women admitted to three tertiary hospitals between 26 May 2009 and 31 December 2009 with laboratory-confirmed influenza A(H1N1)pdm09 infection who were either pregnant or non-pregnant and of childbearing age between 15 and 50 years. Results A total of 222 women, of whom 81 (36.5%) were pregnant, were hospitalized during the study period. Pregnant women were significantly more likely to be hospitalized with influenza A(H1N1)pdm09 infection than non-pregnant women of childbearing age (relative risk 26.3; 95% confidence interval: 20.1–34.6). Among those hospitalized, the proportion of pregnant women having at least one underlying medical condition that could predispose them to influenza-related complications was significantly lower than that of non-pregnant women (32.1% versus 56.0%, P < 0.001). The median time from onset of symptoms to administration of anti-viral drugs was significantly shorter among pregnant women than among non-pregnant women (three days versus five days, P < 0.001). The median length of stay in hospital was also significantly shorter among pregnant women than that of non-pregnant women (two days versus three days, P = 0.002). About 4.9% of pregnant women developed influenza-related complications, compared with 12.8% among non-pregnant women (P = 0.066). Conclusions Pregnant women with influenza A(H1N1)pdm09 infection were at a higher risk of hospitalization. Upon hospitalization, they were not at a higher risk of developing influenza-related complications.